Rare Multidrug-resistant Pseudomonas aeruginosa Identified in a U.S. Deployed Service Member Following Host-nation Medical Treatment. Issue 5 (15th January 2021) - Lawrence, Matthew W; Sachdeva, Mohit; Bennett, Jason W; Menninger, George U; Barrera, Melissa A; Benitez, John G; Kliewer, Maurice L
ABSTRACT: Decision-making related to the utilization of host-nation medical resources in austere forward-deployed environments is complex. Clinical circumstances, local medical intelligence availability, transportation assets, uncertainty regarding standard-of-care variations, military/host-nation funding complications, and regional security concerns all factor into consideration. A case of a U.S. active duty military service member who suffered a cardiac arrest on a military base in Southwest Asia is described in this report. After return of circulation following defibrillation, he was administered thrombolytic therapy for an electrocardiogram-identified ST-elevation myocardial infarction and transported to a local host-nation cardiac hospital for emergent percutaneous coronary intervention. During his subsequent transportation back to the USA, surveillance testing identified that he was colonized with a rare strain of Pseudomonas aeruginosa, demonstrating New Delhi metallo-beta-lactamase-1 and 16S RNA methyltransferase-2 enzymes, which confer significant resistance to carbapenem and aminoglycoside antibiotics, respectively. 1–3 This combination of antibiotic resistance has been reported very rarely in the medical literature and has never been reported within the deployed military health system until now. The risk of exposure to multidrug-resistant organisms was not a factor initially considered in the decision to utilize host-nation medical resources in this case, which provided lesson learned and raised new questions, for future operational medical planning.